2021
DOI: 10.1001/jamapsychiatry.2021.1844
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning Disruptions in Individuals With Depression and Sensitivity to Symptom Change Following Cognitive Behavioral Therapy

Abstract: IMPORTANCE Major depressive disorder is prevalent and impairing. Parsing neurocomputational substrates of reinforcement learning in individuals with depression may facilitate a mechanistic understanding of the disorder and suggest new cognitive therapeutic targets.OBJECTIVE To determine associations among computational model-derived reinforcement learning parameters, depression symptoms, and symptom changes after treatment. DESIGN, SETTING, AND PARTICIPANTS In this mixed cross-sectional-cohort study, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 57 publications
3
54
0
Order By: Relevance
“…Certainly, the subjective values of states that are taught by the subjective reward functions can vary greatly from their objective values, which is problematic if, for instance, the parameters of the subjective reward function change over time. More generally, given that aspiration levels are an interesting lever for the brain to pull on itself, examining its consequences for psychiatric dysfunction in a range of environments [100,101] is an important direction for future research. It would also be worth exploring whether dysfunctions such as anhedonic depression [102][103][104] partly arise because of problems with subjective rather than objective components of reward sensitivity.…”
Section: Relation To Mood and Anhedoniamentioning
confidence: 99%
“…Certainly, the subjective values of states that are taught by the subjective reward functions can vary greatly from their objective values, which is problematic if, for instance, the parameters of the subjective reward function change over time. More generally, given that aspiration levels are an interesting lever for the brain to pull on itself, examining its consequences for psychiatric dysfunction in a range of environments [100,101] is an important direction for future research. It would also be worth exploring whether dysfunctions such as anhedonic depression [102][103][104] partly arise because of problems with subjective rather than objective components of reward sensitivity.…”
Section: Relation To Mood and Anhedoniamentioning
confidence: 99%
“…Depression is also treated with cognitive behavioral therapy (CBT), an efficacious psychotherapy theorized to reduce symptoms in part through changing learning ( 114 ). A recent study found that after 12 weeks of CBT, normalization of reward learning rate occurred in patients with depression alongside improved anhedonia and negative affect ( 148 ). Another fMRI study demonstrates that increased neural activity in the ventral striatum, which is known to contain dense regions of dopaminergic terminals, correlates with increased RPE signaling and response to CBT ( 149 ).…”
Section: Depressionmentioning
confidence: 99%
“…One explanation may be that fear-related symptoms and disorders are more related to these learning differences than distress-related disorders (Clark & Watson, 1991;McTeague & Lang, 2012). Meanwhile, people with anxiety and depression may also learn differently from good versus bad outcomes (Brown et al, 2021;Gagne et al, 2020;Lamba et al, 2020;Wise & Dolan, 2020). The direction of results in individual studies varies; a recent computational meta-analysis suggested that anxiety and depression show greater punishment learning rates (Pike & Robinson, 2022).…”
Section: D Reinforcement Learning Studies Of Anxietymentioning
confidence: 99%